Mechanistic and kinetic studies on biodiesel production catalyzed by an efficient pyridinium based ionic liquid1. Issue 8 (3rd August 2015) - Li, Kaixin; Yang, Zhihong; Zhao, Jun; Lei, Junxi; Jia, Xinli; Mushrif, Samir H.; Yang, Yanhui
<x xml:space="preserve">Abstract</x> A mechanism involving cooperative hydrogen bonds for ionic liquid-catalyzed biodiesel production was proposed and validated by kinetic data.